fragility curves for steel moment frame with welded flange plate connection (Journal of Civil Engineering Researchers, 2022)
The importance of evaluating the performance of structures against earthquakes is not hidden from anyone. It is important to have an overview of the resistance level of the structure to achieve a safe and economical design against the potential input forces. Therefore, a lot of research is always done in this area in different ways.This article contains the method and results of the study of seismic vulnerability for WFP connection which is widely used and pre-approved connection for steel moment frames that Has been introduced in the tenth section of the Iranian building code. The purpose is to draw the fragility curve using numerical methods.Due to the fact that this connection is pre-approved just for medium moment frames, it is necessary to check its reliability if want to use it in a special moment frame. The probability of structural damage caused by seismic force can be presented as a function of ground motion characteristics and various design parameters Using fragility curves. In this study, seven records of earthquake accelerograms were used for incremental nonlinear dynamic analysis (IDA) those most consistent with the site intended for this structure.
Keywords: Fragility curves; incremental nonlinear dynamic analysis; pre-validated connections